Chapter XXI secolo: l’universo fisico-cibernetico e le grandi sfide emergenti - Lombardi, Mauro (Studi e saggi, 2021)
In this chapter we outline the cyber-physical world we entered following the pervasive diffusion of information processing devices that are able to able to interact through exchanging information (cyber-physical systems). In this way ubiquitous computing and ubiquitous connectivity are changing how people think, act and produce. Indeed processes and products are becoming smart and connected on a potentially global level. The possibility of realizing a digital of everything representation from the subatomic level and nanoscale to the astronomical level implies that the physical world is surrounded and pervaded by a digital sphere that interacts with and influences it. Are we in a world like the one hypothesized by Borges' famous paradoxes of the 1: 1 map? The reality Is very different from the imagery Borges’s map: hyperstructures self-organize and emerge, global players act and influence the dynamics of complex adaptive systems.